First record of four Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) species from the southwestern Atlantic - Rodrigues, Thaiana G. A.; Cardoso, Irene A. (Zootaxa, 2019)
New records of Pasiphaea from the Southwestern Atlantic are reported. The material was sampled during the oceanographic projects REVIZEE and HABITATS and four species were collected: Pasiphaea alcocki (Wood-Mason, 1891); P. major Hayashi, 2006; P. taiwanica Komai et al., 2012 and P. tarda Krøyer, 1845. An identification key for the seven currently reported species of southwestern Atlantic Pasiphaea is provided.